Integrated metagenomics unravels the microbial mechanisms driving greenhouse gas and odor emissions during composting - Ruohan Xia; Bin Cui; Guoxue Li; Haibin Zhou; Wenhai Luo; Zhicheng Xu (Bioresource Technology, 2026)

Co-mitigating tire wear particles and their leachates across the life cycle: A critical review - Kejun Liao; Junyi Yu; Ruohan Huang; Wenjing Zhou; Yuwei Zhou; Junru Guo; Shengman Zhang; Chen Cai; Kaiming Peng; Xiangfeng Huang; Jia Liu (Water Research, 2026)

Global inequalities in non-carcinogenic health risks associated with drinking arsenic-contaminated groundwater - Ruohan Wu; Qinchuan Xin; Yin Yang; Ying Sun; Xuewen Zhou; Yongjian Ruan; Kun Xiao; Taiyuan Chen; Jianxiu Qiu (Journal of Hazardous Materials, 2026)

Transformer-Enhanced Instance Segmentation for Automated Crucian Carp Phenotyping Under Controlled Imaging Conditions - Miao Zhu; Ruohan Lu; Yi Zhou; Sisi Yuan; Qiu Xiao; Yu Deng (Fishes, 2026)
Fish phenotyping plays an important role in growth evaluation, selective breeding, and precision aquaculture. Conventional phenotypic measurement methods are labor-intensive, time-consuming, and susceptible to observer variability. To improve measurement efficiency and reproducibility, this study proposes an automated fish phenotyping framework based on Transformer-enhanced instance segmentation. Specifically, a Mask2Former decoder was integrated into the Mask R-CNN architecture to improve boundary delineation and segmentation quality. Based on segmentation outputs, phenotypic parameters, including body length, body height, and projected area, were automatically extracted using PCA-assisted orientation estimation and geometric measurement. In addition, a standardized anatomical landmark annotation framework consisting of 12 reference points was introduced to support reproducible phenotypic description and future extensible morphometric analysis. Body weight was further estimated using polynomial regression based on extracted morphological traits. Experiments were conducted using images from three crucian carp varieties under controlled imaging conditions. The proposed framework achieved 92.7% mAP and 89.4% Boundary IoU, improving segmentation performance over the baseline model. Automated measurement yielded average relative errors of 2.16% for body length and 3.85% for body height, while weight prediction achieved an R2 of 0.9479 and a mean relative error of 7.31%. These results demonstrate that Transformer-enhanced segmentation can support accurate and efficient automated phenotyping under standardized conditions and provide a foundation for future deployment in more complex aquaculture environments.

Analysis of the blowdown of supercritical carbon dioxide from simple vessel - Fengyuan Tian; Minyun Liu; Yanping Huang; Ruohan Zheng; Yangle Wang; Houjun Gong; Yu Tang; Tianzeng Liu; Jinghan Hu; Haohan Yuan; Yuan Zhou (Annals of Nuclear Energy, 2026)

Rambutan-inspired tri-layer architecture with regulated strain and lithium transport for high-capacity and stable lithium storage - Huan Du; Ganggang Ma; Ziqing Yin; Shaoqing Rao; Sheng Lin; Tianyi Zhang; Jingke Ren; Yucai Wu; Wei Zhang; Ruohan Yu; Dongyuan Zhao; Wei Li; et al. (Science Bulletin, 2026)

Effects of microsized and nanosized polystyrene on detrital processing and nutrient dynamics in streams - Jingjing Du; Mengxi Gao; Zhi Rao; Xun Zhou; Yan Su; Jianguo Zhao; Jianxiang Lv; Ruohan Mao; Yuran Song; Xia Cao (Environmental Pollution, 2026)

Co-exposure to multiple fine particulate matter constituents and adults obstructive sleep apnoea (OSA) in Southern China - Suhan Wang; Gongbo Chen; Peipei Dong; Hailin Xiong; Yuewei Liu; Ruohan Zhou; Ranxu Zhang; Qiong Ou (Environmental Pollution, 2026)

Identification of disease-associated gene expression signatures for mechanistic insights and drug prediction in dilated cardiomyopathy-induced heart failure - Wei Yu; Shuai Xu; Xin Tan; Hangyao Zhang; Ruohan Ma; Yiyao Zeng; Anchen Xu; Honghui Tang; Qin Rui; Yahui Song; Yafeng Zhou (Molecular and Cellular Biochemistry, 2026)

Surface nitridation of Si enabled gradient artificial solid electrolyte interface and self-optimized structural evolution - Zhenyi Huang; Ruohan Yu; Jinshuai Liu; Yuxia Zhong; Lei Zhang; Liang Zhou (Science Bulletin, 2025)

Icaritin activates p53 and inhibits aerobic glycolysis in liver cancer cells - Xiangyang Zhou; Di Wu; Tian Mi; Ruohan Li; Tao Guo; Wenjuan Li (Chemico-Biological Interactions, 2024)

Cloud detection from Himawari-8 spectral images using K-means++ clustering with the convolutional module - Kaizheng Wang; Yitong Fu; Shunzhen Zhou; Ruohan Zhou; Gang Wen; Fangrong Zhou; Lulu Li (International Journal of Remote Sensing, 2024)

High dimethylsulfoniopropionate concentrations in the surface seawater over the marginal seas of China and the Northwest Pacific Ocean during May–July of 2021 following La Niña - Lingxiao Li; Zhengguo Cui; Keming Qu; Hongsheng Wang; Ruohan Song; Xiaoke Hu; Shenghui Zhang; Tao Jiang; Mingying Zhou; Qingjing Hu (Marine Pollution Bulletin, 2023)

Alterations in functional network centrality in first-episode drug-naïve adolescent-onset schizophrenia - Ming Zhou; Lihua Zhuo; Ruofei Ji; Yingxue Gao; Hongchao Yao; Ruohan Feng; Lianqing Zhang; Guoping Huang; Xiaoqi Huang (Brain Imaging and Behavior, 2022)

Characteristics and Cause Analysis of Variations in Light Precipitation Events in the Central and Eastern Tibetan Plateau, China, During 1961–2019 - Kaifang Li; Liguo Cao; Zhengchao Zhou; Lei Jiao; Ning Wang; Ruohan Liu (Chinese Geographical Science, 2022)

Structural architecture of Neoproterozoic rifting depression groups in the Tarim Basin and their formation dynamics - Bizhu He; Cunli Jiao; Taizhu Huang; Xingui Zhou; Zhihui Cai; Zicheng Cao; Zhongzheng Jiang; Junwen Cui; Zhuoyin Yu; Weiwei Chen; Ruohan Liu; Xiaorui Yun; et al. (Science China Earth Sciences, 2019)